No increase of serum neurofilament light in relapsing-remitting multiple sclerosis patients switching from standard to extended-interval dosing of natalizumab. (November 2022) - Johnsson, Magnus; Farman, Helen H; Blennow, Kaj; Zetterberg, Henrik; Malmeström, Clas; Axelsson, Markus; Lycke, Jan
Background: Accumulating evidence supports the efficacy of administering natalizumab (NZ) with extended-interval dosing (EID) in patients with relapsing-remitting multiple sclerosis (RRMS). Objectives: We switched NZ dosing from 4-week to 6-week intervals in patients with RRMS, and investigated the effect on serum neurofilament light chain (sNfL) concentrations. Methods: We included two cohorts of patients with RRMS treated with NZ: one received the standard-interval dosing (4 weeks) at baseline, and were switched to 6-week intervals (EID4–6, N  = 45). The other cohort received EID (5- or 6-week intervals) both at baseline and during follow-up (EID5/6, N  = 25). Serum samples were collected in the EID4–6 cohort at every NZ infusion, for 12 months. The primary outcome was the change in sNfL concentrations after switching to EID. Results: The baseline mean sNfL concentration in the EID4–6 cohort was 10.5 ng/L (standard deviation (SD) = 6.1), and it remained unchanged at 12 months. Moreover, individual sNfL concentrations did not change significantly after extending the NZ dosing intervals. In addition, the EID4–6 and EID5/6 cohorts had similar baseline sNfL concentrations. Conclusion: We concluded that extending the NZ dosing interval did not increase axonal damage, as determined with sNfL, in patients with RRMS.